Interpretamos cuentos - Barrantes Alva, Rosina Ysabel (2019)
The present work of pedagogical sufficiency is aimed basically at developing in students their skills to learn how to interpret and explain oral texts, based on the development of methodological strategies related to the recovery of information, explanation and organization in oral texts: determining and explaining the subject, the communicative purpose, emotions and moods of people and characters, as well as the lessons from it, using the relevant information about it._x000D_ The learning session called "We play stories" is designed for third graders from the Juan Pablo II educational institution of trujillo district; in its elaboration, the pedagogical processes of problemization, motivation, recovery of previous knowledge, purpose and organization and accompaniment for the development of skills and the evaluation of learnings such as processes have been taken into account related to the before, during and after hearing oral texts, with the aim of fostering the active and committed participation of students in the construction of meaningful learnings, using as an instrument for collecting valid and reliable information from the Checklist.